1990
DOI: 10.1038/jcbfm.1990.87
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of the Computerized Brain Atlas Programme for Localization and Quantification in Positron Emission Tomography

Abstract: Summary:The computerized brain atlas programme (CBA) provides a powerful tool for the anatomical anal ysis of functional images obtained with positron emission tomography (PET). With a repertoire of simple transfor mations, the data base of the CBA is first adapted to the anatomy of the subject's brain represented as a set of magnetic resonance (MR) or computed tomography (CT) images. After this, it is possible to spatially standardize (reformat) any set of tomographic images related to the subject, PET images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 29 publications
1
69
1
1
Order By: Relevance
“…As described earlier in more detail (Seitz et al, 1990(Seitz et al, , 1997, the rCBF images were transformed into standard brain anatomy using transformation parameters determined for each individual. Standardization yielded 21 axial image slices that were 6.43 mm apart with a matrix of 128 ´ 128 pixels of 2.55 ´ 2.55 mm each.…”
Section: Discussionmentioning
confidence: 99%
“…As described earlier in more detail (Seitz et al, 1990(Seitz et al, , 1997, the rCBF images were transformed into standard brain anatomy using transformation parameters determined for each individual. Standardization yielded 21 axial image slices that were 6.43 mm apart with a matrix of 128 ´ 128 pixels of 2.55 ´ 2.55 mm each.…”
Section: Discussionmentioning
confidence: 99%
“…PET studies that have demonstrated activation of the cerebellum include those examining motor learning [Seitz et al, 1990], motor control [Fox et al, 1985], and tactile learning [Roland et al, 1987], as well as somatosensory discrimination [O'Sullivan et al, 1994]. It has been postulated that the cerebellum is involved in higher cognitive processing mediated through its reciprocal connections with the prefrontal cortex [Middleton and Strick, 1994].…”
Section: Cerebellummentioning
confidence: 99%
“…The subject-to-subject, and test-to-test variability in the reference atlas was minimized by standardizing the measurement parameters and conforming all scans to a standard space. 25,26 In our study, it was necessary to minimize the variation in the stimulus by using an MRI compatible method that applied a consistently repeatable stimulus. Whereas breath-holding and inhalation of carbogen (5% CO 2 in oxygen) are inexpensive, simple, and MRI compatible, they do not reliably result in consistent end-tidal 27,28 or arterial values 29 (see, ref.…”
Section: Main Findingsmentioning
confidence: 99%